2011
DOI: 10.1007/s11434-011-4702-x
|View full text |Cite
|
Sign up to set email alerts
|

p53-dependent upregulation of PIG3 transcription by γ-ray irradiation and its interaction with KAP1 in responding to DNA damage

Abstract: PIG3 (p53-inducible gene 3), originally identified as one of a set of genes induced by p53 before the onset of apoptosis, was assumed to contribute to early cellular response to DNA damage. Here, we studied the relation between p53 status and the increased expression of PIG3 by ionizing radiation (IR), and the related clues regarding the involvement of PIG3 in the cellular response to IR-induced DNA damage signaling. We demonstrated that the pentanucleotide microsatellite sequence was responsible for the p53-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This was the first evidence suggesting the involvement of PIG3 in the IR-induced DNA damage response. We also observed that PIG3 formed specific ionizing radiation-induced foci (IRIF) colocalized with γ-H2AX foci and partially with pKAP-17. J-H Lee et al extensively investigated the participation of PIG3 in DNA damage checkpoints after UV irradiation or after treatment using the radiomimetic drug neocarzinostatin (NCS) 8.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…This was the first evidence suggesting the involvement of PIG3 in the IR-induced DNA damage response. We also observed that PIG3 formed specific ionizing radiation-induced foci (IRIF) colocalized with γ-H2AX foci and partially with pKAP-17. J-H Lee et al extensively investigated the participation of PIG3 in DNA damage checkpoints after UV irradiation or after treatment using the radiomimetic drug neocarzinostatin (NCS) 8.…”
Section: Introductionmentioning
confidence: 84%
“…PIG3 has been recently reported to participate in DNA damage response induced by UV radiation and the radiomimetic drug neocarzinostatin 8, and by ionizing radiation 7. One of the mechanistic pathways for PIG3 to function in DDR is to prompt a large scale chromatin relaxation in response to DNA damage signaling 7. It is well known that PIKK family members, including DNA-PKcs, ATM and ATR, play important roles in this DNA damage signaling process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…KRAB-associated protein (KAP-1), also known as tripartite motif-containing 28 (TRIM28), is a critical effector in ATM-dependent chromatin relaxation in response to DNA DSBs induced by ionizing radiation (IR). Qin et al [5] report that p53-inducible gene 3 (PIG3), also known as tumor protein p53-inducible protein 3 (TP53I3), formed foci in the nucleus after IR-induced DNA DSB, and that this protein interacted and partially colocalized with phospho-KAP-1 foci. PIG3 must play a role in large-scale chromatin relaxation in DNA damage signaling.…”
mentioning
confidence: 99%